Presentation - Rodríguez Chávez, Iván (2021)
The eighth issue of Archivo Vallejo. Revista de Investigación del Rectorado de la Universidad Ricardo Palma gathers the second part of the papers presented at the IV International Congress "Vallejo Siempre" (New York, September 30-October 2, 2021).